HENS’ ORGANISM RESPONSE TO THE CHANGE OF THE HEIGHT OF CAGE BATTERY LOCATION - Osadcha, Yu. V. (Scientific Progress & Innovations, 2021)
Increasing the tier structure of cage equipment to 12–15 tiers is one of the modern ways of resource conservation in poultry farming and is often used by producers to obtain more products from 1 m2 of premise space. However, there are no data on the impact of such housing on the physiological state of hens, and the current rules of VNTP-APK-04.05. for keeping hens in cages are designed for 1–3-tier cage batteries. The aim of this work was to study the physiological state of hens based on the analysis of changes in their blood picture indicators depending on the height of cage batteries’ location. For this purpose, in the conditions of a modern complex for the production of food eggs in one poultry house, 4 groups of hens were formed, each of which was kept on a separate floor-analogue in terms of area and cage equipment. Each floor was equipped with “Big Dutchman” 3-tier cage batteries (Germany), consisting of 1,176 cages with an area of 40,544 cm2. The cages batteries of each floor were separated from each other by a grate-type floor so that tiers 1–3 were included to the 1st floor, tiers 4–6 – to the 2nd, tiers 7–9 - to the 3rd, and tiers 10–12 – to the 4th floor of the cage equipment. The laying hens’ blood picture was determined on Micros 60 hematology ana-lyzer, for which 30 whole blood samples were taken from laying hens of each group at the age of 52 weeks. It was found that the increase in the height of cage batteries location was not reflected in the hemograms of hens, which may indicate the absence of a negative impact of increasing the tier structure of cage equipment. Whereas, keeping hens in cages of a multi-tiered cage battery on the first floor (1–3 tier) was accompanied by changes in hemogram parameters characteristic of the stressful state of the body, namely an increase in the number of leukocytes in the blood by 29.0–73.2 % (3.5>normal), erythrocytes – by 14.3–18.5 %, ESR – by 26.0–46.5 % and a decrease in thrombocytes concentration by 12.8–14.8%, as well as the upsetting of the ratio of different leukocytes’ forms– an increase in the concentration heterophils by 6.8–13.5 % (4.5 % > normal) against the background of a decrease in monocytes by 1.8–2.5 % (1.2 % <normal), lymphocytes – by 1.7–8.4 %, eosinophils – by 1.7–1.9 % and basophils by 0.9–1.4 %. The obtained results are the basis for finding the causes of stress development in hens at their keeping on the low floor of the cage equipment.